Polyamine metabolism during the growth cycle of tobacco BY-2 cells - Gemperlová, Lenka; Eder, Josef; Cvikrová, Milena (Plant physiology and biochemistry, 2005)
We studied polyamine (PA) biosynthesis, oxidation and conjugation in asynchronously dividing cells of tobacco BY-2 cell suspension culture (Nicotiana tabacum L.) during 7-day growth cycle. We analyzed the levels of free and conjugated PAs and the activities of biosynthetic and catabolic enzymes during the subculture interval. The contents of free spermidine and spermine started to increase after the inoculation into the fresh medium, positively correlated with the mitotic activity of BY-2 cells and reached their maxima at the beginning of exponential phase on day 3. On the contrary, the endogenous level of free Put showed a transient decline in the lag-phase, and then increased till the end of exponential phase (day 5). The time-course of the content of PCA-soluble conjugates showed a trend similar to that of the free PAs. The inoculation of BY-2 cells into the fresh medium resulted in a sharp increase in the activities of ornithine decarboxylase (ODC, EC 4.1.1.17) and S-adenosylmethionine decarboxylase (SAMDC; EC 4.1.1.50). Arginine decarboxylase (ADC; EC 4.1.1.19) activity remained low during the whole subculture interval. The rise of diamine oxidase (DAO; EC 1.4.3.6) in the first day after subculture coincided with the decrease in free Put level. De novo synthesis of PAs in BY-2 cells after inoculation into the fresh medium and the participation of both PA conjugation with hydroxycinnamic acids and Put oxidative degradation in maintaining of free PA levels during the growth cycle are discussed.
Keywords: Biogenic Polyamines; biogenní polyaminy; buněčné dělení; Cell Line; Perchlorates; Amine Oxidase (Copper-Containing); Nicotiana; perchloráty; ornithindekarboxylasa; Ornithine Decarboxylase; buněčné linie; Cell Division; tabák; Solubility; rozpustnost; histaminasa